2015
DOI: 10.1111/psyp.12435
|View full text |Cite
|
Sign up to set email alerts
|

Visual search is postponed during the period of the AB: An event‐related potential study

Abstract: (2015) 'Visual search is postponed during the period of the AB : an event-related potential study. ', Psychophysiology., 52 (8). pp. 1031-1038.Further information on publisher's website:https://doi.org/10.1111/psyp.12435Publisher's copyright statement: This is the accepted version of the following article: Lagroix, H. E. P., Grubert, A., Spalek, T. M., Di Lollo, V. and Eimer, M. (2015), Visual search is postponed during the period of the AB: An event-related potential study. Psychophysiology, 52(8): 1031-103… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
18
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 43 publications
5
18
0
Order By: Relevance
“…In contrast, the boost-and-bounce and eSTST models suggest that during the blink, inhibitory processes bring activation below baseline levels, such that the onset of attentional engagement is unaffected, but the maximal enhancement generated by T2 is weaker. Building on our conclusion that the N2pc can be used as a proxy of attentional engagement, our results support an intermediary position between these accounts: since the onset of the N2pc was delayed and the N2pc amplitude attenuated, we conclude that attentional engagement is both delayed (by approximately 20-30ms, see also Lagroix et al, 2015) and suppressed during the blink.…”
Section: Implications For the Attentional Blink Literaturesupporting
confidence: 76%
See 2 more Smart Citations
“…In contrast, the boost-and-bounce and eSTST models suggest that during the blink, inhibitory processes bring activation below baseline levels, such that the onset of attentional engagement is unaffected, but the maximal enhancement generated by T2 is weaker. Building on our conclusion that the N2pc can be used as a proxy of attentional engagement, our results support an intermediary position between these accounts: since the onset of the N2pc was delayed and the N2pc amplitude attenuated, we conclude that attentional engagement is both delayed (by approximately 20-30ms, see also Lagroix et al, 2015) and suppressed during the blink.…”
Section: Implications For the Attentional Blink Literaturesupporting
confidence: 76%
“…On the one hand, we found that the attentional blink did not modulate the location benefit produced by a spatial cue (thus replicating Bae et al, 2018;Ghorashi et al, 2009a;2009b;2010;Zivony & Lamy, 2016). On the other hand, we found the AB to reduce the likelihood of identifying the distractor letter inside this cue (as indicated by the smaller response-compatibility effect observed during the blink) and to both delay the onset (see also, Lagroix et al, 2015) and reduce the amplitude (see also, e.g., Dell'Acqua et al, 2006;Jolicoeur et al, 2006a) of the N2pc component. Taken together, these results demonstrate that the N2pc does not reflect attentional shifting (which, unlike the N2pc, is unaffected by the blink) but processes that occur downstream from attentional shifting (e.g., identification, see also Foster et al, 2018;.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…There is reasonable agreement on the role of the dorso-and ventrolateral prefrontal cortices in the generation of P3a (e.g., Ranganath & Rainer, 2003). Indeed, these current results are in broad agreement with evidence indicating the involvement of the frontoparietal network in enabling attentional selection of task-relevant information, both when displayed simultaneously with arrays of spatially distributed distracting information (Corbetta, 1998;Todd & Marois, 2004;Xu & Chun, 2006;Yantis et al, 2002) and when embedded in a spatially overlapping, but temporally distributed, sequence of distracting events (Dell'Acqua, Sessa, Jolicoeur, & Robitaille, 2006;Husain, Shapiro, Martin, & Kennard, 1997;Joseph, Chun, & Nakayama, 1997;Lagroix, Grubert, Spalek, Di Lollo, & Eimer, 2015;Marcantoni, Lepage, Beaudoin, Bourgouin, & Richer, 2003;Marois, Chun, & Gore, 2000). There is also good agreement that more posterior regions, including the temporoparietal junction and inferotemporal cortices, are likely involved in the generation of P3b (e.g., Polich, 2003Polich, , 2007.…”
Section: Discussionsupporting
confidence: 90%
“…Observers were required to make a speeded response to T2, and then identify T1 at leisure. RT has been used as the response measure in earlier studies of the AB (e.g., Jolicoeur & Dell'Acqua, 1998;Lagroix, Grubert, Spalek, Di Lollo, & Eimer, 2015;Zuvic, Visser, & Di Lollo, 2000) for two main reasons. First, RT is free from possible confounds arising from response-ceiling constraints inherent in the 100% limit of the accuracy scale (e.g., Ghorashi, Enns, Spalek, & Di Lollo, 2009).…”
mentioning
confidence: 99%